A resting EEG study of neocortical hyperexcitability and altered functional connectivity in fragile X syndrome - Wang, Jun (J Neurodev Disord, 2017)
BACKGROUND: Cortical hyperexcitability due to abnormal fast-spiking inhibitory interneuron function has been documented in fmr1 KO mice, a mouse model of the fragile X syndrome which is the most common single gene cause of autism and intellectual disability. METHODS: We collected resting state dense-array electroencephalography data from 21 fragile X syndrome (FXS) patients and 21 age-matched healthy participants. RESULTS: FXS patients exhibited greater gamma frequency band power, which was correlated with social and sensory processing difficulties. Second, FXS patients showed increased spatial spreading of phase-synchronized high frequency neural activity in the gamma band. Third, we observed increased negative theta-to-gamma but decreased alpha-to-gamma band amplitude coupling, and the level of increased theta power was inversely related to the level of resting gamma power in FXS. CONCLUSIONS: Increased theta band power and coupling from frontal sources may represent a mechanism providing compensatory inhibition of high-frequency gamma band activity, potentially contributing to the widely varying level of neurophysiological and behavioral abnormalities and treatment response seen in full-mutation FXS patients. These findings extend preclinical observations and provide new mechanistic insights into brain alterations and their variability across FXS patients. Electrophysiological measures may provide useful translational biomarkers for advancing drug development and individualizing treatments for neurodevelopmental disorders with associated neuronal hyperexcitability. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11689-017-9191-z) contains supplementary material, which is available to authorized users.